Multisensory experiences at travel fairs: What evokes feelings of pleasure, arousal and dominance among visitors?. Issue 1 (1st January 2022) - Sihvonen, Jenniina; Turunen, Linda Lisa Maria
Abstract: This exploratory study concerns the evocation of multisensory experiences at travel fairs. In this context, stimulation of the senses is vital in engendering feelings of pleasure, arousal and dominance. The purpose of this study is to explore the ways in which travel fairs evoke multisensory experiences and internal responses in consumer visitors. To accomplish this task we gathered ethnographic data (pictures, videos and audio recordings) together with interview data from visitors, and applied the classic stimulus-organism-response conceptualization to the data analysis. The findings contribute to existing knowledge concerning the management of retail atmospherics in shedding light on customer experiences beyond (dis)-satisfaction in the little studied context of travel fairs. Our findings imply that the travel fair encompasses visually dominant stimuli whereas tactile stimuli are somewhat lacking. Although visitors to these fairs seem to find the experience manageable and pleasurable, the aspect of excitement is somewhat lacking. We suggest that the visually dominant environment that is characteristic of fairs should move in a multisensory direction in terms of offering visitors experiences that are more appealing. It is also crucial to manage the volume and intensity of senses effectively to prevent information overload and sensory overstimulation. Supplemental data for this article is available online at https://doi.org/10.1080/15470148.2021.1949417 .